2010
DOI: 10.1111/j.1464-410x.2009.08995.x
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive percutaneous cystolithotomy: an effective treatment for bladder stones in infants aged <1 year

Abstract: Study Type – Therapy (case series)
Level of Evidence 4 OBJECTIVE To present our experience with minimally invasive percutaneous cystolithotomy (MPCCL) for the treatment of bladder stones in infants aged <1 year. PATIENTS AND METHODS From 1 January 2003 to 31 October 2008, 15 boys with a mean (range) age of 8.2  (3.0–11.5) months underwent MPCCL. The mean (range) stone diameter was 1.4 (0.9–2.2) cm. Ten infants had a solitary stone while five had more than one stone. MPCCLs were performed under general anaesthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 20 publications
(23 reference statements)
1
7
0
1
Order By: Relevance
“…Multiple studies reported its use in normal paediatric bladders harbouring variable‐sized stones [3,25–27]. Also, it was performed safely in infants aged as young as 3 months [28]. Similar to our results, the commonly reported complications were persistent suprapubic fluid extravasation and intraperitoneal fluid collection [3,26].…”
Section: Discussionsupporting
confidence: 86%
“…Multiple studies reported its use in normal paediatric bladders harbouring variable‐sized stones [3,25–27]. Also, it was performed safely in infants aged as young as 3 months [28]. Similar to our results, the commonly reported complications were persistent suprapubic fluid extravasation and intraperitoneal fluid collection [3,26].…”
Section: Discussionsupporting
confidence: 86%
“…25 Isen et al, reported their experience with pneumatic CL in children with a mean age of 7.6yrs (range, 3 -14). The mean stone size was 14mm (range, [8][9][10][11][12][13][14][15][16][17][18][19][20]. The operating time was 22min (range, 10-46 min).…”
Section: Discussionmentioning
confidence: 99%
“…The final published version may differ from this proof. of 25min and mean hospital stay of 2.8 days 19. However, PCCL has important disadvantages, such as the presence of an incision, the need to dilate a tract, the insertion of a suprapubic tube, and the need for a urethral catheter which leads to relatively longer hospital stay when compared with CL.…”
mentioning
confidence: 99%
“…It is not mandatory to be an endourologist or a super professional urologist to do this method; furthermore, it does not need any unusual instruments and it can be done in every urology operating room even with limited facilities. 21,22…”
Section: Discussionmentioning
confidence: 99%